Effects of varying longitudinal bending stiffness in running shoes on lower limb biomechanics of elite marathon runners - Yang, Hailiang; Cai, Yuhui; Li, Kuang; Wang, Xiangdong; Liu, Tao (Frontiers in Sports and Active Living, 2025)
ObjectiveThis study examined the effect of three levels of longitudinal bending stiffness (LBS) in carbon-plated shoes on lower limb biomechanics.MethodsFifteen elite male marathon runners, each with a personal best under 3 h, participated in the study. They were tested wearing shoes with three LBS levels: low (LLBS, 0.31 Nm/deg), medium (MLBS, 0.40 Nm/deg), and high (HLBS, 0.48 Nm/deg). All participants ran at a constant speed of 4.76 m/s. Kinematic and kinetic data were synchronously collected using the VICON motion capture system and three AMTI force plates. Angular parameters of the ankle, knee, hip, and metatarsophalangeal (MTP) joints were calculated using the sagittal plane coordinate system. Joint moments and joint work (positive and negative) at each lower limb joint were analyzed using the built-in inverse dynamics module in Visual3D.ResultsIn terms of kinematics, the maximum dorsiflexion angle of the MTP joint during the late stance phase and the range of motion during the stance phase was significantly lower in the MLBS to HLBS shoes than in the LLBS shoes. Negative work at the MTP joints was significantly higher in the LLBS shoes than in the HLBS shoes (LLBS: 0.21 ± 0.05 J/kg, MLBS: 0.16 ± 0.03 J/kg, HLBS: 0.13 ± 0.05 J/kg, F = 12.053, p = 0.001). Additionally, the maximum hip extension moment was also significantly affected by LBS (F = 6.561, p = 0.012, η2 = 0.286), with the MLBS (1.49 ± 0.27 Nm/kg) shoes showing lower values than both LLBS (1.80 ± 0.33 Nm/kg, p = 0.021) and HLBS (1.58 ± 0.32 Nm/kg, p = 0.047). The MLBS shoes significantly increased positive work at the ankle joint (LLBS: 0.66 ± 0.08 J/kg, MLBS: 0.71 ± 0.10 J/kg, HLBS: 0.69 ± 0.08 J/kg, F = 3.292, p = 0.047).ConclusionsThis study demonstrates that increasing the LBS shoes alters the lower limb biomechanical performance of elite marathon runners. Both MLBS and HLBS conditions reduced MTP joint dorsiflexion, but MLBS shoes significantly increased positive work at the ankle joint and improved joint function while maintaining lower hip joint moments. Among the three conditions, MLBS better balanced mechanical efficiency and natural joint function, suggesting it may be a more biomechanically suitable option for elite marathon runners. These findings provide valuable insights for optimizing LBS in performance shoe design, with MLBS offering a potential advantage in both biomechanical performance and injury prevention.